A phase 2 trial of single low doses of rasburicase for treatment of hyperuricemia in adult patients with acute leukemia. (August 2021) - Vachhani, Pankit; Baron, Jeffrey; Freyer, Craig W.; Miller, Austin; Wetzler, Meir; Thompson, James E.; Griffiths, Elizabeth A.; Wang, Eunice S.
Highlights: Rasburicase is a synthetic urate oxidase that oxidates uric acid to allantoin which is more soluble in urine than uric acid. Rasburicase can be expensive especially when administered as per the recommended dosage of 0.2 mg/kg/day for up to 5 days. Single doses of rasburicase (1.5−3 mg) in addition to adjunct measures are safe and efficacious for prevention and treatment of TLS. Abstract: Background: Rasburicase can markedly and rapidly decrease uric acid (UA) levels, thereby preventing and treating tumor lysis syndrome. However, rasburicase is expensive, especially when used as per the manufacturer's recommended dosage of 0.2 mg/kg/day for up to 5 days. Numerous reports have shown that lower, and even single doses are effective in lowering UA levels but prospective randomized studies comparing low doses have not been performed. Objectives: To prospectively determine the efficacy and safety of two single low doses of rasburicase in adult patients (pts) with acute leukemia and elevated plasma UA. Methods: Eligible pts aged ≥ 18 years old with acute leukemia and UA ≥ 7.5 mg/dL were randomized to receive an initial single dose of rasburicase 1.5 mg (Arm A) or 3 mg (Arm B) on day 1 in an unblinded fashion. All pts received allopurinol 300 mg daily on days 1–6. Results: Twenty-four pts (median age 69 years; 14 males and 10 females) were enrolled in this phase 2 study (12 on each arm). Twenty pts had acute myeloid leukemia while 3 had acute lymphoblastic leukemia, and 1 had acute promyelocytic leukemia. Median initial UA level was 9.8 mg/dL. Eighty-three percent of pts in both arms achieved UA < 7.5 mg/dL by 24 h after therapy. Five pts (21 %; 2 from Arm A and 3 from Arm B) required additional doses of rasburicase. The majority (23/24) of pts achieved UA goals after 1–2 doses of rasburicase. None had worsening renal function. Both doses were well tolerated, and no treatment related adverse events were reported. Conclusions: Single doses of rasburicase (as low as 1.5−3 mg) used in addition to allopurinol were well tolerated and highly efficacious (83 % response rate) in decreasing UA levels within 24 h of administration in adult acute leukemia pts with hyperuricemia.